Cryo-analytical STEM of frozen, aqueous dispersions of nanoparticles. (May 2019) - Ilett, Martha; Brydson, Rik; Brown, Andy; Hondow, Nicole
Highlights: First demonstration of elemental mapping of nanoparticles in vitreous ice. Spatially resolved STEM-EDX and EELS to identify liquid-based phenomena. Comparison of cryo-TEM and cryo-STEM conditions. Abstract: In situ characterisation of nanoparticle dispersion and surface coatings is required to further our understanding of the behaviour of nanoparticles in aqueous suspension. Using cryogenic transmission electron microscopy (cryo-TEM) it is possible to analyse a nanoparticle suspension in the frozen, hydrated state; however, this analysis is often limited to imaging alone. This work demonstrates the first use of analytical scanning TEM (STEM) in the examination of nanoparticles captured in a layer of vitreous ice. Imaging and analysis of frozen hydrated suspensions by both STEM energy dispersive X-ray (EDX) spectroscopy and electron energy loss spectroscopy (EELS) under cryogenic conditions demonstrates the identification and separation of CeO2, Fe2 O3, ZnO and Ag nanoparticles in suspension. Damage caused by the electron beam was shown to occur at far higher electron fluences in STEM (<2000 e − /Å 2 ) compared to CTEM (<100 e − /Å 2 ) due to diffusion limited damage by the radiolysis products generated in vitreous ice. Further application of cryo-analytical STEM was undertaken on barium titanate biomarker nanoparticles dispersed in cell culture media to show the formation of a Ca and P rich coating around the nanoparticles when suspended in the media. This previously unreported coating changes the surface chemistry of the biomarkers when exposed to cells. Thus we show that the technique has the potential to advance our understanding of the fundamental behaviour of nanoparticles in complex aqueous suspensions.